Large-grain CH3NH3PbI3 film by incorporation of urea in one-step solution process. (November 2018) - Bazzazzadegan, Hadi; Mortazavi, Yadollah; Khodadadi, Abbasali; Mohagheghian, Maryam
Abstract: The Lewis acid–base adduct is a comprehensive approach to modify crystallinity and surface morphology of perovskite, nevertheless, the key role of adduct in nucleation and growth mechanism is ambiguous. In our study, it was revealed that the size of perovskite colloidal clusters considerably increase when urea adds to the solution and this phenomenon controls the nucleation. In addition, the intermediate structures formed by urea govern the final perovskite morphology through retarding the perovskite crystal growth. Thus, large-grain CH3 NH3 PbI3 (MAPbI3 ) film with almost full surface coverage achieves by the incorporation of urea especially when antisolvent technique is applied during the spin coating. Finally, extremely large grains, larger than 100 micrometers, form via simultaneous use of dimethyl sulfoxide (DMSO) and urea in perovskite solution. Graphical abstract: Through formation of adduct intermediates which retard the crystal growth rate, larger crystal grains of perovskite are formed. Highlights: For the first time, urea is introduced as a potential Lewis base that could form adduct with perovskite precursors. Through formation of new perovskite intermediates, excellent crystallinity & full coverage of perovskite film was achieved. The addition of DMSO in urea/perovskite precursors led to formation of very large grains of perovskite.